Analysis of syphilis hospitalizations numbers in elderly women in Brazil between 2010 and 2019 by age group (Research, Society and Development, 2022)
Objective: To describe the trend in syphilis hospitalization rates in elderly women in Brazil between 2010 and 2019. Methodology: This is a descriptive ecological study, which used data taken from the Health Information System (TABNET), in the SUS Hospital Morbidity tab by Place of Residence, covering the whole Brazil. Results: Overall, 389 hospitalizations for syphilis were recorded. The 60 to 69 age group accounted for most records, with 215 notifications. In contrast, the group that grew the most in this period was the 70 to 79 year olds, with an increase of 1033.3%. Furthermore, 2019 was the year with the most records, with 91 notifications. Finally, in 2011, there were 9 hospitalizations, representing the lowest number of cases. Conclusion: The results reinforce the need to promote awareness and information strategies to this population and sensitize health professionals to have an investigative look for suspicion, allowing diagnosis of syphilis in the elderly woman and avoiding outcomes of greater severity of the disease.